Universal screening for familial hypercholesterolemia in children: The Slovenian model and literature review. (October 2018) - Groselj, Urh; Kovac, Jernej; Sustar, Ursa; Mlinaric, Matej; Fras, Zlatko; Podkrajsek, Katarina Trebusak; Battelino, Tadej
Abstract: Background and aims: Familial hypercholesterolemia (FH) is arguably the most common monogenic disorder in humans, but severely under-diagnosed. Individuals with untreated FH have an over 10-fold elevated risk of cardiovascular complications as compared to unaffected individuals; early diagnosis and timely management substantially reduce this risk. Slovenia has gradually implemented the program of universal FH screening in pre-school children, consisting of a two step approach: (1) universal hypercholesterolemia screening in pre-school children at the primary care level; (2) genetic FH screening in children referred to the tertiary care level according to clinical guidelines (with additional cascade screening of family members). The program is presented in detail. Methods: We analyzed retrospective data (2012–2016), to assess the efficiency of the universal FH screening program. In that period, 280 children (59.3% female) were referred to our center through the program for having TC > 6 mmol/L (231.7 mg/dL) or >5 mmol/L (193.1 mg/dL), with a positive family history of premature cardiovascular complications at the universal hypercholesterolemia screening. Results: 170 (57.1% female) of them were fully genotyped, 44.7% had an FH disease-causing variant (28.8% in LDLR gene, 15.9% in APOB, none in PCSK9 ), one patient was LIPA positive, and 40.9% of the remaining patients carried an ApoE4 isoform; genetic analysis is still ongoing for one-third of the referred patients. For almost every child with confirmed FH, one parent had highly probable FH. Conclusions: FH was confirmed in almost half of the referred children, detected through the universal screening for hypercholesterolemia. Highlights: FH is a common monogenic disorder but severely under diagnosed and under treated. FH screening in childhood with early treatment is needed. Slovenia has a unique and effective program of universal FH screening in children. Almost half of the children referred through the program had FH causing mutation.